Sacrifices humains Perspectives croisées et représentations - Bonnechere, Pierre; Gagné, Renaud (Religions, 2013)
The topic of human sacrifice, which tends to provoke both fascination and disgust, leaves few people indifferent and remains a highly contested academic issue. The present volume is not concerned with the historical reality of human sacrifice, a question that continues to divide historians and anthropologists. Rather, it is interested in how different ancient cultures represented human sacrifice differently, both theirs and that of others, either as an event or a symbol. How does a society confront what might have been -or what it thought was- its own cruel and bloody past? What are the culturally specific values through which human sacrifice was understood in each group, and how did they differ in the case of other related practices, such as anthropophagy? How have these perceptions changed over time, and how have they adapted to the transformations of ideology? The core of the volume is concerned with the abundantly detailed material of ancient Greece. The Greek evidence and its interpretation are challenged by various articles on the ancient practice and its representation in other ancient cultures, China, Aztec Mesoamerica, and imperial Rome, which offer fundamentally different viewpoints, and provide a myriad of occasions for reflecting on contrast and the need to constantly question the fundamental terms of our analysis.